Are interleukin-15 and -22 a new pathogenic factor in pustular palmoplantar psoriasis? - Lesiak, Aleksandra; Bednarski, Igor; Pałczyńska, Marta; Kumiszcza, Ewelina; Kraska-Gacka, Marzena; Woźniacka, Anna; Narbutt, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Pustular palmoplantar psoriasis (PPP) is a rare type of psoriasis affecting mainly distal parts of the limbs. Despite numerous theories about etiology of PPP, the pathogenesis still remains unclear. Recent data indicate that interleukin (IL)-15, IL-17 and IL-22 enhance a proinflammatory response in certain skin inflammatory diseases such as psoriasis and atopic dermatitis. There is also evidence that anti-endomysial (anti-EMA) and anti-gliadin (AGA) antibodies are engaged in PPP development. Aim : To assess IL-15, IL-17, IL-22 serum levels and evaluate the presence of anti-endomysial and anti-gliadin antibodies in patients with PPP. Material and methods : The study group consisted of 20 females of the mean age of 51.8 suffering from PPP. Additionally 29 healthy individuals, age and sex matched, served as controls. ELISA was performed to evaluate serum IL-15, IL-17, IL-22 concentrations while an indirect immunofluorescence test (IIF) was used to determine anti-EMA and AGA presence. Results: The mean value of IL-15 and IL-22 serum concentrations was significantly higher in the study group than in the control group (IL-15: 6.48 vs. 4.88 pg/ml; IL-22: 81.47 vs. 4.90 pg/ml, respectively; p < 0.05 for all comparisons). The IL-17 serum level in the study group was higher when compared to the control group (2.0 vs. 0.75 pg/ml), however the results were not statistically significant (p = 0.26). There were no anti-EMA and AGA antibodies detected, both in the control and study group. Conclusions : The results obtained may suggest involvement of IL-15 and IL-22 in the pathogenesis of PPP.